Mystery of the flying express - Dixon, Franklin W. (New York, Grosset & Dunlap, 2002)
After the new hydrofoil they are guarding is stolen, the Hardy boys face frequent danger in solving a mystery involving criminals who operate by signs of the zodiac.
Keywords: Mystery and detective stories